(untitled) (Филолошки студии, 2019)
The paper deals with the semantics of indefinite pronouns with the prefix po- in the Croatian language (poneki, pokoji) and the prefix no- in the Macedonian language (понекоj, понешто) as well as their functions within the limits of the category of definiteness/indefiniteness. Grammatical descriptions do not regard these pronouns as indefinite ones, while their usage in modern texts testifies to the fact of their having specific functions. Pronouns with the prefix ро-/по- are usually used in the contexts of weak definiteness and existentiality, but are never used in the contexts of uncertainty. In the existentional meaning they cannot be used in situations with an unknown participant, but are widely presented in the situation of distributivity, in the plan of the future time and in the situation-alternative. Besides, in their existentional usage the pronouns acquire an additional meaning of sporadicity, dispersion in time and space, a small or approximate number of singled-out elements. The usage of the ро- /по-pronouns within noun-groups of generic status is very rare. As to the category of number, the pronouns in question are plurally-marked, and their usage in plural noun-phrases is redundant, that is why singular nounphrases with a pronoun related to a plural denotate are prevailing in texts.